PREDICTION MODEL OF DIVIDEND PAYMENT OF CZECH JOINT STOCK COMPANIES - Sejkora, František (My University, 2016)
The dividend payment is the very important part of investment decision for many stockholders. Results of this text identify finance factors that influence the management in dividend policy within the examined branch “Production and distribution of electric energy, gas and water”. Seven regressive models were created and they identify and define the effect of individual factors on the dividend payment among individual owner´s types. The retained earnings, the rate of return of invested assets in total and the size of company have the positive effect on the dividend payment. For the purpose of better interpretation the individual factors were quantified in form of the chance that the company will pay the dividend when compared to the fact that the company is not going to pay any dividend. The resulting regressive model was subsequently validated using the classification table and the receiver operating characteristic curve.
PREDIKČNÍ MODEL VÝPLATY DIVIDEND ČESKÝCH AKCIOVÝCH SPOLEČNOSTÍ
Keywords: dividend policy; factors; management; model; dividendová politika; faktory; management; model